The effect of preoperative deep breathing exercise with incentive spirometer initiated in the preoperative period on respiratory parameters and complications in patients underwent open heart surgery: a randomized controlled trial - Hatice Öner Cengiz; Zeynep Uluşan Özkan; Eylem Gani (BMC Anesthesiology)
Abstract Background Incentive spirometer is used in lung expansion therapy to maintain alveolar patency and improve pulmonary volumes in postoperative cardiac surgical patients. Deep breathing exercises with an incentive spirometer significantly reduce the development of postoperative pulmonary complications after open-heart cardiac surgery. Aim To determine the effect of deep breathing exercises with an incentive spirometer initiated in the preoperative period on respiratory parameters and complications in patients who underwent open-heart surgery. Methods This randomized controlled study was conducted with a total of 66 participants. The participants were randomized into a deep breathing group (n = 32) and a control group (n = 34). The control group received hospital routine physiotherapy, and the deep breathing group started to perform deep breathing exercises with an incentive spirometer in the preoperative period. Data were collected with the Sociodemographic and Medical Data Form and Patient Follow-up Form (respiratory rate, oxygen saturation (SpO2) level, arterial blood gas parameters and posteroanterior chest X-ray were monitored with this form prepared by the investigators). The Medical Research Council Scale was used to determine the severity of dyspnea in the patients included in the study. Primary outcomes included respiratory rate, oxygen saturation, arterial blood gas parameters, posteroanterior chest X-ray, and evaluation of postoperative pulmonary complications development. Secondary outcomes included the mechanical ventilation time, length of intensive care unit stay, and length of hospital stay. Results The incidence of postoperative pulmonary complications was 3.1% and 23.5% (p < 0.05) in the deep breathing and control groups, respectively. The mechanical ventilation time, length of hospital stay, and length of stay in the intensive care unit were significantly shorter in the deep breathing group (p < 0.05). In the deep breathing group, the mean SpO2 values evaluated before surgery, on the first day in the Cardiovascular Surgery Unit, and on the day of discharge were significantly higher than the control group (p < 0.05). Conclusion Deep breathing exercises with an incentive spirometer initiated in the preoperative period contribute to a reduction in postoperative pulmonary complication rates, shortening of mechanical ventilation time, length of stay in the intensive care unit, length of hospital stay, and improvement of pre- and postoperative oxygenation. Trial registration The trial was registered on June 17, 2022, at https://www.clinicaltrials.gov/ , registration number NCT05428722.